Hemopatch® is effective and safe to use: real-world data from a prospective European registry study - Lombardo, Carlo; Lopez-Ben, Santiago; Boggi, Ugo; Gutowski, Piotr; Hrbac, Tomas; Krska, Lukas; Marquez-Rivas, Javier; Russello, Domenico; York, Elisa; Zacharias, Mario (Updates in surgery, 2022)
Surgical procedures are often impeded by bleeding and/or leakage of body fluids. These complications cannot always be resolved by conventional surgical techniques. Hemopatch® is a hemostatic patch that also functions as a sealant. Here we document the effectiveness and safety of Hemopatch® for routine procedures of multiple surgical disciplines. To this end, we performed a prospective, multicenter, single-arm, observational registry study. Patients were eligible if they had received Hemopatch® during an open or minimally invasive procedure in one of these specialties: hepatobiliary, cardiovascular, urological, neurological/spinal, general, or lung surgery. Patients were excluded if they had a known hypersensitivity to bovine proteins or brilliant blue, intraoperative pulsatile or severe bleeding and/or infection at the target application site (TAS). The primary endpoint for intraoperative effectiveness was hemostasis assessed as the percentage of patients achieving hemostasis within 2 min and the percentage of patients achieving hemostasis without re-bleeding at the time of surgical closure. The registry enrolled 621 patients at 23 study sites in six European countries. Six hundred twenty patients had completed follow-up information. Hemostasis within 2 min was achieved at 463 (74.5%) of all 621 TASs. Hemostasis without re-bleeding was observed at 620 (99.8%) TASs. Adverse events were reported in 64 patients (10.3%). This Hemopatch® registry shows that Hemopatch® efficiently establishes hemostasis and sealing in a variety of surgical specialties, including minimally invasive procedures. Furthermore, we provide evidence for the safety of Hemopatch® across all the specialties included in the registry. This study is registered at clinicaltrials.gov: NCT03392662.
Keywords: Cattle; Animals; krvácení při operaci; skot; obory chirurgické; hemostatika; výsledek terapie; Blood Loss, Surgical; Registries; lidé; Specialties, Surgical; Treatment Outcome; Hemostasis, Surgical; prospektivní studie; Prospective Studies; registrace; zvířata; hemostáza chirurgická; Hemostatics; Humans